Female subjects in black and white: Race, psychoanalysis, feminism - Abel, Elizabeth; Christian, Barbara; Moglen, Helene (University of California Press, 1997)
This landmark collaboration between African American and white feminists goes to the heart of problems that have troubled feminist thinking for decades. Putting the racial dynamics of feminist interpretation center stage, these essays question such issues as the primacy of sexual difference, the universal nature of psychoanalytic categories, and the role of race in the formation of identity. They offer new ways of approaching African American texts and reframe our thinking about the contexts, discourses, and traditions of the American cultural landscape. Calling for the racialization of whiteness and claiming that psychoanalytic theory should make room for competing discourses of spirituality and diasporic consciousness, these essays give shape to the many stubborn incompatibilities―as well as the transformative possibilities―between white feminist and African American cultural formations. Bringing into conversation a range of psychoanalytic, feminist, and African-derived spiritual perspectives, these essays enact an inclusive politics of reading. Often explosive and always provocative, Female Subjects in Black and White models a new cross-racial feminism.
Keywords: afro-féminisme; amériques; approches et analyses; cours; discipline; fem1000; femmes* afro-américaines; féminismes noirs; littérature; premier cycle; psychanalyse; ressource en ligne; régions géographiques; sciences humaines; états-unis; études littéraires

Répertoire des œuvres des compositrices du Québec au XXe siècle - Labelle, Nicole (Centre de recherche en civilisation canadienne-française, 1997)
Keywords: 1900-1999; DIG; amériques; art; discipline; femmes* artistes; histoire des femmes*; histoire et politique; musique; périodes historiques; québec; ressource en ligne; régions géographiques; thématiques; travail

Fields of play: Constructing an academic life - Richardson, Laurel W. (Rutgers University Press, 1997)
Comment les circonstances spécifiques dans lesquelles nous écrivons affectent-elles ce que nous écrivons ? Comment ce que nous écrivons affecte-t-il ce que nous devenons ? Comment pouvons-nous maintenir l'intégrité professionnelle et personnelle dans l'université d'aujourd'hui ? Dans une série d'écrits traditionnels et expérimentaux, aboutissement de dix années de travaux en cours, Laurel Richardson enregistre un parcours intellectuel, déplaçant les frontières et créant de nouvelles façons de lire et d'écrire. Appliquant l'imaginaire sociologique au processus d'écriture, elle relie sa vie à son travail. Profondément engageant, écrit de manière émouvante avec grâce, élégance et clarté, le livre stimule les lecteurs à situer leur propre écriture dans des contextes personnels, sociaux et politiques.
Keywords: 1900-1999; 1990-1999; amériques; arts; cours; discipline; fem1000; littérature; premier cycle; périodes historiques; régions géographiques; thématiques; théories féministes; écriture des femmes*; états-unis; études littéraires

La critique féministe étatsunienne en musique : pertinence en milieu francophone Québécois - Sabourin, Carmen (Canadian University Music Review / Revue de musique des universités canadiennes, 1997)
L’auteure examine la pertinence de la critique féministe étasunienne en musique en milieu francophone québécois. Dans un premier temps, elle propose une réflexion critique sur le féminisme étasunien en musique. Puis, elle pose la question de la pertinence de ses fondements et de ses méthodologies pour les jeunes musicien(ne)s issus du milieu culturel francophone du Québec qui, au moment d’entreprendre des études avancées, envisageraient de se consacrer à la recherche sur la pensée féministe.
Keywords: DIG; amérique du nord; amériques; arts; canada; discipline; débat; féminisme étasunien; musique; québec; ressource en ligne; régions géographiques; théories féministes

Contre-voix : essais de critique au féminin - Saint-Martin, Lori (Collection Essais critiques, 1997)
Keywords: 1900-1999; 1990-1999; amériques; arts; cours; cycles supérieurs; discipline; fem1000; fem7000; lit2815; lit3220; lit3495; littérature; premier cycle; périodes historiques; québec; régions géographiques; thématiques; théories féministes; écriture des femmes*; études littéraires

Feminisms: An anthology of literary theory and criticism - Warhol, Robyn R.; Price Herndl, Diane (Rutgers University Press, 1997)
This volume brings together 58 previously published essays on 19th and 20th century British and North American texts that were written from the mid-1970s to 1990 by feminist literary critics. These essays cover a variety of critical perspectives, including Anglo-American, French, Marxist, structuralist, new historicist, and psychoanalytic. The 13 sections of the book cover various issues in feminist criticism: institutions, methodologies, canon, tradition, body, desire, reading, discourse, ethnicity, history, class, men, and autobiography. Each section includes essays addressing the intersections of feminist concern with questions of class, race, sexual preference, and nationality. Contributors include Barbara Christian, Sandra M. Gilbert, Susan Gubar, Helene Cixous, and Elaine Showalter
Keywords: 1900-1999; amériques; anthologie; arts; cours; cycles supérieurs; discipline; europe; fem1000; fem7000; histoire et politique; lit3220; littérature; premier cycle; périodes historiques; royaume-uni; régions géographiques; thématiques; théories féministes; états-unis; études littéraires